Nilai Pendidikan Karakter dalam Naskah Soal Bahasa Indonesia di SMP Negeri 3 Kota Ternate - Nurbaya, Nurbaya; Samad, Sartika; Buang, Defi (Peneliti.net, 2024)
This study aims to describe, analyze, and interpret data and information about the analysis of the odd semester exam question scripts in the Indonesian language subject at SMP Negeri 3 Ternate City. This research method is a qualitative research method. This study aims to find out and describe in detail about Character Education in the Indonesian Language exam question scripts at SMP Negeri 3 Ternate City. Data collection techniques are the process of observation, interviews and questionnaires. Data analysis techniques use data reduction techniques, data presentation, and drawing conclusions. The results of the study showed that of the 18 characters proposed by (Permendikbud 2018) and Hartono (2014, pp. 262-263) there were only 10 characters tested in the odd semester exam question scripts for class VIII SMP Negeri 3 Ternate City. The eighteen characters include religious, honest, tolerant, disciplined, hard working, creative, independent, democratic, curious, national spirit, love of the homeland, respect for achievement, friendly/communicative, love of peace, love of reading, care for the environment, care for society, and responsibility